Doping – problem nieświadomego społeczeństwa i polityki międzynarodowej państw - Pepłowska, Aleksandra (Kultura-Społeczeństwo-Edukacja, 2022)
The definition of doping in the World Anti-Doping Code is an important instrument of international politics. While implications are obvious for the professional athletes participating in Olympic Games, they remain vague for the broader society – the followers of the Olympic struggles. The article is an attempt to indicate the problem faced by society, international institutions and states, trying to pursue an effective anti-doping policy. It presents a comprehensive description of one of the largest doping scandals with the participation of the Russian authorities in 2013–2014 and the results of the author’s research on society’s knowledge of doping in sports. Public awareness of banned substances and methods may turn out to be crucial while assessing the actions of governments and international institutions. Society may have insufficient knowledge about doping and may be unaware of its role in politics on an international scale. An ani-doping policy is a part of state policy, so it impacts the way of benefiting physical culture which is one of the areas creating the public sector.